Une troisième voie entre l'État et le marché - Antona , Martine; Bousquet , François (éditions Quae, 2017)
Following the trip to France by the 2009 Nobel Prizewinner in Economic Sciences, Elinor Ostrom, the authors of this work set out her teaching based on her direct interactions with the public. It is an entire critique of conventional economic theories that is expressed and a renewal of social sciences thinking that is taking place. Elinor Ostrom developed an alternative path to the State and the market in her work and experiences; this targeted desirable trajectories for the social and ecological systems.